The Effect of Basic Life Support (BLS) Video on Police’s Self-Efficacy in Delivering First Aid Support of Traffic Emergency at Denpasar City: Pengaruh Video Bantuan Hidup Dasar (BHD) Terhadap Self-Efficacy Polisi Dalam Melakukan Pertolongan Pertama Kegawatdaruratan Lalu Lintas Di Kota Denpasar - I Gusti Ngurah Juniartha; Saputra, I Kadek (Bali Medika Jurnal, 2022)
Traffic emergencies are events that cannot be predicted in advance and can be experienced by all age groups who drive motorized vehicles. It is noted that over the last few years, the number of motor vehicle accidents in Denpasar has increased which has an impact on increasing morbidity and/or mortality. In addition to the high number of accidents in Denpasar, the first victim's response also plays an important role for the condition of the next victim. To overcome this, it is necessary to have a standby bystander close to the scene of the incident. One of the bystanders is the involvement of the police. The next problem is the ignorance of the police in the process of providing Basic Life Support (BLS) in the pandemic era which causes them to lack courage and confidence in providing assistance, resulting in victims experiencing disability or death. The purpose of this study was to determine the effect of Basic Life Support (BLS) Video on police self-efficacy in carrying out first aid for traffic emergencies in the city of Denpasar. This research is included in a quantitative study with a one group pre-test post-test design and a cross-sectional approach. This research was conducted for 1 month with the number of respondents as many as 87 police officers using a simple random sampling technique on the entire police population selected from 4 areas in the city of Denpasar. Sampling data was collected using a questionnaire to measure self-efficacy before and after being given BLS video. During the pre test, police self-efficacy was in the moderate range as many as 78 respondents (89.7%), after being given the intervention there was a significant increase to the high range as many as 53 respondents (60.9%). So it can be concluded that the provision of BLS video is effective and be able to increase police self-efficacy in carrying out first aid for traffic emergencies in the city of Denpasar.